Smartphone addiction and academic procrastination among college students: a serial mediation model of self-control and academic self-efficacy - Zhao, Xiuli; Wang, Huahua; Ma, Zaoming; Zhang, Libing; Chang, Tian (Frontiers in Psychiatry, 2025)
IntroductionResearches have highlighted the individual roles of smartphone addiction (SA), self-control (S-C), and academic self-efficacy (AS-E) in predicting academic procrastination (AP), but studies on how these variables combine to affect AP are scarce. Drawing inspiration from the conceptual model of procrastination, this research endeavors to examine a serial mediation model in which SA serves as a precursor, with S-C and AS-E acting as serial mediators in predicting AP among college students who are prone to it.MethodsParticipants were 1269 Chinese undergraduates (989 females, Mage = 19.03±1.00) from seven major regions in China. Data were collected using an online questionnaire. Descriptive and mediation analyses were conducted in SPSS 25.0.ResultsThe findings revealed that SA is indirectly linked to AP through independent and sequential mediation by S-C and AS-E. People with high SA reported lower levels of S-C, which in turn was associated with lower AS-E, and these were associated with higher reports of AP.DiscussionThese findings offer significant contributions to the current body of research on AP, laying the groundwork for the development of interventions focused on reducing AP among college students.